Second Hit Phenomenon and Timing of Definitive Fracture Fixation After Damage Control Laparotomy: A Narrative Review - Saoud Javed; Jabbar Ghufran Syed; Aaron Robinson; Syed Muhammad Nadir Raza; Alia Aamir; Farwa Saleem (Journal of Health, Wellness and Community Research, 2026)
Background: The second hit phenomenon describes the worsening of systemic inflammatory stress when major surgery is performed after severe trauma and remains a central concern in determining the timing of definitive fracture fixation in polytrauma patients. This issue is especially complex in patients undergoing damage control laparotomy, in whom the presence of an open abdomen has traditionally been viewed as a reason to defer definitive orthopaedic intervention. Objective: To review contemporary evidence on the second hit phenomenon and evaluate current concepts regarding the timing of definitive fracture fixation after damage control laparotomy, with emphasis on the transition from time-based to physiology-guided decision-making. Methods: A narrative review of approximately 12 peer-reviewed publications from 2016 to 2024 was undertaken, focusing on studies and conceptual papers addressing polytrauma physiology, damage control orthopaedics, early appropriate care, safe definitive surgery, open abdomen management, and factors influencing operative timing. Results: The reviewed literature demonstrated a clear shift away from rigid time-based fixation strategies toward individualized decisions guided by physiological markers such as lactate, base deficit, hemodynamic stability, coagulation status, and temperature. Although damage control orthopaedics remains appropriate in unstable patients, delayed fixation may increase instability-related and infectious complications. Limited but important evidence suggests that early definitive fixation can be performed safely in selected patients with an open abdomen when physiological recovery has been achieved. Conclusion: Definitive fracture fixation after damage control laparotomy should be guided primarily by physiological readiness rather than elapsed time or abdominal closure status alone.
Keywords: Second hit phenomenon, polytrauma, damage control laparotomy, fracture fixation timing, damage control orthopaedics